KACA: Educational Tutorial Video-Based Games to Stimulate Early Childhood Language Skills - Winardi, Diva Winding Seciola Syakhinna; Widiana, I Wayan (Universitas Pendidikan Ganesha, 2024)
Several findings regarding children's difficulties in reading show that out of a total of 11 children in the class, 8 of them still experience difficulties in initial reading. In addition, researchers also noted that the main reason for these difficulties was due to the slow process of letter recognition in these children. This research aims to develop the